Decoding the enigma: unveiling the transmission characteristics of waterfowl-associated blaNDM-5-positive Escherichia coli in select regions of China - Zhang, Shaqiu; Shu, Yanxi; Yang, Zhechen; Zhong, Zhijun; Wang, Mingshu; Jia, Renyong; Chen, Shun; Liu, Mafeng; Zhu, Dekang; Zhao, Xinxin; Wu, Ying; Yang, Qiao; et al. (Frontiers in Microbiology, 2024)
Escherichia coli (E. coli) serves as a critical indicator microorganism for assessing the prevalence and dissemination of antibiotic resistance, notably harboring various antibiotic-resistant genes (ARGs). Among these, the emergence of the blaNDM gene represents a significant threat to public health, especially since carbapenem antibiotics are vital for treating severe infections caused by Gram-negative bacteria. This study aimed to characterize the antibiotic resistance features of blaNDM-5-positive E. coli strains isolated from waterfowl in several regions of China and elucidate the dissemination patterns of the blaNDM-5 gene. We successfully isolated 103 blaNDM-5-positive E. coli strains from 431 intestinal fecal samples obtained from waterfowl across five provincial-level units in China, with all strains exhibiting multidrug resistance (MDR). Notably, the blaNDM-5 gene was identified on plasmids, which facilitate efficient and stable horizontal gene transfer (HGT). Our adaptability assays indicated that while the blaNDM-5-positive plasmid imposed a fitness cost on the host bacteria, the NDM-5 protein was successfully induced and purified, exhibiting significant enzymatic activity. One strain, designated DY51, exhibited a minimum inhibitory concentration (MIC) for imipenem of 4 mg/L, which escalated to 512 mg/L following exposure to increasing imipenem doses. This altered strain demonstrated stable resistance to imipenem alongside improved adaptability, correlating with elevated relative expression levels of the blaNDM-5 and overexpression of efflux pumps. Collectively, this study highlights the horizontal dissemination of the blaNDM-5 plasmid among E. coli strains, confirms the associated fitness costs, and provides insights into the mechanisms underlying the stable increase in antibiotic resistance to imipenem. These findings offer a theoretical framework for understanding the dissemination dynamics of blaNDM-5 in E. coli, which is essential for developing effective strategies to combat carbapenem antibiotic resistance.